Kebebasan Beragama sebagai Pilar Moderasi: Analisis QS. Al-Baqarah 2:256 dalam Tafsir Al-Majid An-Nur - Mahda, Mahda; Afifah, Nor; Sa’adah, Nismah; Jannah, Nisa Ghina Raudatul; Dasuki, Akhmad; Mahfuzh, Taufik Warman (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Religious freedom in Indonesia plays a vital role in preserving social harmony and peace among people of diverse faiths. Although the Constitution guarantees every citizen the right to choose and practice their religion, challenges often emerge in reality, including social tensions arising from religious differences. This study examines Hasbi Ash-Shiddieqy’s interpretation of QS. Al-Baqarah verse 256 in Tafsir Al-Majid an-Nur as a basis for understanding the Islamic concept of religious freedom. It also explores how his perspective aligns with the human rights principles recognized in Indonesia. Employing a qualitative descriptive method through a library research approach, this study analyzes both the tafsir text and relevant scholarly works. The findings reveal that Hasbi Ash-Shiddieqy underscores the Qur’anic notion that religion must not be imposed, as genuine faith originates from personal conviction and inner awareness rather than external coercion. His interpretation links religious freedom with the value of moderation, which advocates tolerance, respect for diversity, and the pursuit of social harmony in a plural society. Ultimately, Hasbi’s thought reinforces Islam’s image as an inclusive religion that upholds individual freedom in faith, serving as a crucial pillar in fostering a just, peaceful, and respectful community.